Heterogeneous Hydrogel Structures with Spatiotemporal Reconfigurability using Addressable and Tunable Voxels. Issue 10 (25th January 2021) - Khodambashi, Roozbeh; Alsaid, Yousif; Rico, Rossana; Marvi, Hamid; Peet, Matthew M.; Fisher, Rebecca E.; Berman, Spring; He, Ximin; Aukes, Daniel M.
Abstract: Stimuli‐responsive hydrogels can sense environmental cues and change their volume accordingly without the need for additional sensors or actuators. This enables a significant reduction in the size and complexity of resulting devices. However, since the responsive volume change of hydrogels is typically uniform, their robotic applications requiring localized and time‐varying deformations have been challenging to realize. Here, using addressable and tunable hydrogel building blocks—referred to as soft voxel actuators (SVAs)—heterogeneous hydrogel structures with programmable spatiotemporal deformations are presented. SVAs are produced using a mixed‐solvent photopolymerization method, utilizing a fast reaction speed and the cononsolvency property of poly( N ‐isopropylacrylamide) (PNIPAAm) to produce highly interconnected hydrogel pore structures, resulting in tunable swelling ratio, swelling rate, and Young's modulus in a simple, one‐step casting process that is compatible with mass production of SVA units. By designing the location and swelling properties of each voxel and by activating embedded Joule heaters in the voxels, spatiotemporal deformations are achieved, which enables heterogeneous hydrogel structures to manipulate objects, avoid obstacles, generate traveling waves, and morph to different shapes. Together, these innovations pave the way toward tunable, untethered, and high‐degree‐of‐freedom hydrogel robots that can adapt and respond to changing conditions in unstructured environments. Abstract : Creating hyper‐redundant miniaturized soft robots with multiple active degrees of freedom is challenging. Using building blocks called soft voxel actuators (SVAs) in a muscle‐inspire bottom‐up manufacturing strategy, hyper‐redundant soft robots are created, demonstrating spatiotemporal reconfigurability and thus ability to work in unstructured environments. A facile mixed‐solvent photopolymerization developed for poly( N ‐isopropylacrylamide) hydrogels supports the mass production of SVAs.